2003
DOI: 10.1159/000074890
|View full text |Cite
|
Sign up to set email alerts
|

PMN/Platelets Coinfused in Guinea Pig Hearts Exposed to Low-Flow Ischemia Have no Additive Cardiodepressive Effect

Abstract: Recent studies revealed an additive cardiodepressive effect of polymorphonuclear granulocytes (PMN) and thrombocytes in hearts exposed to a no-flow ischemia. To find out whether or not this is also true for isolated guinea pig hearts exposed to a low-flow ischemia, the current study was performed. PMN or thrombocytes, together or separately, were applied as a 1-min bolus (1,000/µl or 20,000/µl, respectively) during ischemia or in reperfusion in the presence of thrombin (0.3 U/ml perfusate). Recovery of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, there are opposing studies as well. Seligmann et al did not observe an additional effect of simultaneous applications of platelets and neutrophils over sole application of either of both in a study using isolated guinea pig hearts (76). In contrast, indications for a role of platelet neutrophil interactions in IRI were also found by different inhibition approaches of the P-selectin-P-selectin glycoprotein ligand 1(PSGL1) axis that led to alleviation of myocardial IRI.…”
Section: Leukocyte-platelet-interactions In Irimentioning
confidence: 99%
“…However, there are opposing studies as well. Seligmann et al did not observe an additional effect of simultaneous applications of platelets and neutrophils over sole application of either of both in a study using isolated guinea pig hearts (76). In contrast, indications for a role of platelet neutrophil interactions in IRI were also found by different inhibition approaches of the P-selectin-P-selectin glycoprotein ligand 1(PSGL1) axis that led to alleviation of myocardial IRI.…”
Section: Leukocyte-platelet-interactions In Irimentioning
confidence: 99%
“…For instance, simultaneous infusion of neutrophils and platelets during reperfusion of ischemic isolated guinea pig and rat hearts impaired cardiac function [ 20 , 29 , 49 ]. In line, blocking PNC-formation attenuated these adverse cardiac effects [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on isolated guinea pig hearts by Seligmann et al did not find an additional effect in the combined presence of platelets and neutrophils over the presence of only one cell type alone, questioning a causative role of PLC in IRI. 129 Furthermore, in a conference abstract, Starz et al reported that mice carrying a selective deletion of platelet P-selectin (P-selectin −/− bone marrow chimeras) display a blunted surge in circulating PLC after induction of experimental myocardial IRI. However, this did not result in any differences in infarct size, tissue inflammation, or long-term ejection fraction in comparison to P-selectin WT.…”
Section: Heterocellular Interactionsmentioning
confidence: 99%